Discussion on Party Building Work of Electric Power Enterprises under New Situation - Lv, Jianguang (Journal of Theory and Practice of Social Science, 2023)
The Party building of electric power enterprises is an important content in the development of electric power enterprises. Under the new situation, the traditional Party building of electric power enterprises can not meet the requirements of the new era. Therefore, it is necessary for electric power enterprises to further promote the party building, which is also the basic guarantee for the development of electric power enterprises in the scientific direction. Based on this, this paper expounds the important significance of party building in electric power enterprises under the new situation, discusses and analyzes the key points of party building in electric power enterprises under the new situation, and discusses the party building strategy in electric power enterprises under the new situation.